New records of brackish water Rotifera and Cladocera from Mexico - Sarma, S. S. S.; Nandini, S.; Ramírez García, Pedro; Cortés Muñoz, Juana E. (HIDROBIOLÓGICA, 2017)
Zooplankton samples collected monthly from various parts of the brackishwater lagoon Macoacan in the State of Tabasco during the years 1995-1997 revealed the occurence of 37 rotifer species and two cladoceran species of which five rotifers viz. Platyias leloupi, Ploesoma hudsoni, Synchaeta bicornis, S. hyperborea and Trichocerca marina and one cladoceran viz. Moina minuta are new to Mexican fauna. The recorded species are ilustrated and aspects of their distribution are presented.